Evaluation of the Self-development Training Program as a Guidance and Counseling Service for Enhancing Independence and Resilience in Children with Intellectual Disabilities - Islam, Andi Fajrul; Pandang, Abdullah; Harum, Akhmad (IKIP Siliwangi, 2025)
his study aims to examine the levels of independence and resilience in children with intellectual disabilities and to evaluate the effectiveness of the Self-Development Training program at SLB-C YPPLB Makassar in enhancing these two-character traits. The research employed a mixed-methods approach with an explanatory sequential design. The sample consisted of five children with mild intellectual disabilities selected through purposive sampling. Data were collected using questionnaires (quantitative) and interviews (qualitative). The results showed a significant improvement in independence and resilience, shifting from predominantly low to entirely high levels after participating in the program. The findings conclude that Self-Development Training effectively enhances the independence and resilience of children with intellectual disabilities. This study implies that the Self-Development Training program holds strong potential to be integrated as an essential component of educational services in special schools, particularly in fostering character development among children with intellectual disabilities.